Assessment of thermal characteristics in diverse lithium-ion battery enclosures and their influence on battery performance - Lindsay, Mahiban; Emimal, M. (International Journal of Applied Power Engineering (IJAPE), 2025)
Battery technology is an emerging research domain within the automotive sector, with a focus on various battery chemistries such as Li-ion, LiFePO4, NMC, and NaCl, as well as specialized cells like LiSOCl2. These chemistries are crucial in advancing electric vehicle (EV) battery technology. Batteries are available in different packaging formats, including prismatic, cylindrical, and pouch designs, each tailored to diverse operational environments. This study investigates the impact of these various battery packages on overall battery performance. Additionally, it assesses the influence of temperature on battery efficiency, aiming to identify the optimal temperature range for maximum performance. A significant part of the research focuses on the development of efficient battery thermal management (BTM) systems, which are designed to control and maintain battery temperature within the desired range, thereby enhancing efficiency. The outcomes of this study provide valuable insights for improving the reliability and efficiency of EV batteries. These findings are crucial for ensuring optimal battery performance and safety across different field conditions. Automotive manufacturers and battery suppliers can leverage these insights to refine their product designs, ensuring the dependability and safety of EV batteries. By enhancing battery performance through improved packaging and effective thermal management, this research contributes significantly to the advancement of EV technology, making electric vehicles more reliable and efficient for consumers.